2017
DOI: 10.3945/jn.116.242560
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Iodine Concentration Is a More Accurate Biomarker of Iodine Status Than Urinary Iodine Concentration in Exclusively Breastfeeding Women

Abstract: Iodine status in populations is usually assessed by the median urinary iodine concentration (UIC). However, iodine is also excreted in breast milk during lactation; thus, breast milk iodine concentration (BMIC) may be a promising biomarker of iodine nutrition in lactating women. Whether the mammary gland can vary fractional uptake of circulating iodine in response to changes in dietary intake is unclear. We evaluated UIC and BMIC as biomarkers for iodine status in lactating women with a wide range of iodine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 53 publications
8
104
2
Order By: Relevance
“…UIC was measured in spot urine samples, which is known to have large intra-individual variability [41]. It is also important to acknowledge that BMIC is a more accurate biomarker of iodine status than UIC in lactating women [42]. …”
Section: Discussionmentioning
confidence: 99%
“…UIC was measured in spot urine samples, which is known to have large intra-individual variability [41]. It is also important to acknowledge that BMIC is a more accurate biomarker of iodine status than UIC in lactating women [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Iodine is a critical micronutrient during the first 1000 days of life . Iodine in breast milk is highly variable depending upon maternal iodine intake . In iodine‐sufficient populations, if iodine intake is borderline, iodine is preferentially partitioned into breast milk to safeguard infant requirements .…”
Section: Potential Sources Of Excessive Iodine Exposurementioning
confidence: 99%
“…3,4,15,[44][45][46] Iodine in breast milk is highly variable depending upon maternal iodine intake. 47,48 In iodine-sufficient populations, if iodine intake is borderline, iodine is preferentially partitioned into breast milk to safeguard infant requirements. 47 High breast milk iodine concentration (BMIC) is reported in areas with excess iodine intakes.…”
Section: Breast Milk and Infant Formulaementioning
confidence: 99%
See 1 more Smart Citation
“…The iodine content of breastmilk varies with maternal iodine intake and breastfed infants are therefore highly sensitive to variations in maternal dietary iodine intake [16,17]. There is no established cut-off value for BIC, however, some studies have suggested that BIC ≥100 µg/L may be considered as adequate [16][17][18].…”
Section: Introductionmentioning
confidence: 99%